Energy level alignment in molecular tunnel junctions by transport and spectroscopy: self-consistency for the case of alkyl thiols and dithiols on Ag, Au, and Pt electrodes - Xie, Zuoti; Bâldea, Ioan; Frisbie, C. Daniel (Journal of the American Chemical Society, 2019)
We report here an extensive study of transport and electronic structure of molecular junctions based on alkyl thiols (CnT; n = 7, 8, 9, 10, 12) and dithiols (CnDT; n = 8, 9, 10) with various lengths contacted with different metal electrodes (Ag, Au, Pt). The dependence of the low-bias resistance (R) on contact work function indicates that transport is HOMO-assisted (p-type transport). Analysis of the current-voltage (I-V) characteristics for CnT and CnDT tunnel junctions with the analytical single-level model (SLM) provides both the HOMO-Fermi energy offset εhtrans and the average molecule-electrode coupling (Γ) as a function of molecular length (n), electrode work function (Φ), and the number of chemical contacts (one or two). The SLM analysis reveals a strong Fermi level (EF) pinning effect in all the junctions, i.e., εhtrans changes very little with n, Φ, and the number of chemical contacts, but Γ depends strongly on these variables. Significantly, independent measurements of the HOMO-Fermi level offset (εhUPS) by ultraviolet photoelectron spectroscopy (UPS) for CnT and CnDT SAMs agree remarkably well with the transport-estimated εhtrans. This result provides strong evidence for hole transport mediated by localized HOMO states at the Au-thiol interface, and not by the delocalized σ states in the C-C backbones, clarifying a long-standing issue in molecular electronics. Our results also substantiate the application of the single-level model for quantitative, unified understanding of transport in benchmark molecular junctions.
Gesehen am 07.01.2020